The Causal Relationship between Exports and Economic Growth in Jordan (Global Journal of Management and Business Research, 2014)
This study aims to examine the causal relationship between economic growth and exports in Jordan using the Granger methodology in order to determine the direction of the relationship between the two variables during the period 2000-2012. The study found that there is a causal relationship going from the economic growth to Export, and not vice versa. Based on the outcome of causality tests, the changes in the economic growth help explain the changes that occur in the Export.
Keywords: exports; economic growth; the causal relationship; gdp; granger; jordan